Caracterização geomorfológica do sistema deposicional do Rio Miranda (borda sul do Pantanal mato-grossense, MS) com base em dados orbitais - Merino, Eder Renato [UNESP] (2011)
The Pantanal depositional tract has several fluvial megafans created by rivers with drainage basins in the adjacent plateaus. The Miranda's is one of least known among all the depositional systems in the Pantanal. The scope of this study is to characterize the Miranda river geomorphology and to recognize evidence of paleoenvironmental and paleohydrological changes. To reach these objectives, the following steps were developed: 1) digital processing of orbital data, such as satellite and SRTM data; 2) delimitation and geomorphological subdivision of the depositional system of the Miranda river; 3) integration and interpretation of data, with identification of current and relict depositional landforms; 4) recognition of environmental changes. Three zones were recognized within the system: a confined river plain, an active depositional lobe and an abandoned depositional lobe. The Principal Components Analysis (PCA), applied to the images of satellites, Landsat-7 ETM + and ASTER, resulted in enhancement of relief features. The SRTM data, allowed the recognition of amalgamated depositional landforms inside the alluvial plain, different generations of active and abandoned meanders belts, as well as distributaries paleolobes, were recognized